Cell type-specific Nogo-A gene ablation promotes axonal regeneration in the injured adult optic nerve - Vajda, Flóra; Jordi, N.; Dalkara, D.; Joly, S.; Christ, F.; Tews, Björn; Schwab, M. E.; Pernet, V. (Cell death and differentiation, 2015)
Nogo-A is a well-known myelin-enriched inhibitory protein for axonal growth and regeneration in the central nervous system (CNS). Besides oligodendrocytes, our previous data revealed that Nogo-A is also expressed in subpopulations of neurons including retinal ganglion cells, in which it can have a positive role in the neuronal growth response after injury, through an unclear mechanism. In the present study, we analyzed the opposite roles of glial versus neuronal Nogo-A in the injured visual system. To this aim, we created oligodendrocyte (Cnp-Cre+/−xRtn4/Nogo-Aflox/flox) and neuron-specific (Thy1-Cretg+xRtn4flox/flox) conditional Nogo-A knock-out (KO) mouse lines. Following complete intraorbital optic nerve crush, both spontaneous and inflammation-mediated axonal outgrowth was increased in the optic nerves of the glia-specific Nogo-A KO mice. In contrast, neuron-specific deletion of Nogo-A in a KO mouse line or after acute gene recombination in retinal ganglion cells mediated by adeno-associated virus serotype 2.Cre virus injection in Rtn4flox/flox animals decreased axon sprouting in the injured optic nerve. These results therefore show that selective ablation of Nogo-A in oligodendrocytes and myelin in the optic nerve is more effective at enhancing regrowth of injured axons than what has previously been observed in conventional, complete Nogo-A KO mice. Our data also suggest that neuronal Nogo-A in retinal ganglion cells could participate in enhancing axonal sprouting, possibly by cis-interaction with Nogo receptors at the cell membrane that may counteract trans-Nogo-A signaling. We propose that inactivating Nogo-A in glia while preserving neuronal Nogo-A expression may be a successful strategy to promote axonal regeneration in the CNS.
published online 26 September 2014
Gesehen am 12.02.2021